Low back and neck and shoulder pain in members and non-members of adolescents' sports clubs: The Finnish Health Promoting Sports Club (FHPSC) Study. - Rossi MK; Pasanen K; Kokko S; Alanko L; Heinonen OJ; Korpelainen R; Ravonen K; Selänne H; Vasankari T; Kannas L; Kujala UM; Villberg J; et al. (My University, 2022)
Background
The objective of this study was to investigate the prevalence of self-reported low back pain (LBP) and neck and shoulder pain (NSP), and the related factors in members and non-members of adolescents’ sports clubs.
Methods
This cross-sectional study was based on surveys of 14–16-year-olds as a part of the Finnish Health Promoting Sports Club (FHPSC) Study. The surveys on self-reported health behaviours, injuries, and musculoskeletal health were conducted among sports club members (n = 962) and non-members (n = 675). Binary logistic regression analysis was applied to study the associations between dependent variables of LBP and NSP, and the independent factors.
Results
The prevalence of LBP during the preceding 3 months was 35.0 % in girls and 24.5 % in boys (p < 0.05 for sex difference). The prevalence of NSP was 55.9 % in girls and 27.3 % in boys (p < 0.001 for sex difference). Being a sports club member increased the odds for LBP in boys (odds ratio [OR] 2.35, 95 % CI 1.48–3.72). On the other hand, sports club participation was associated with lower odds of frequent NSP in girls (OR 0.52, 95 % CI 0.33–0.82). No associations were found between other leisure-time physical activity and LBP or NSP. Higher screen time (computer games, TV/DVD, phone, Internet) during leisure-time increased the odds of NSP in boys and LBP in boys and girls.
Conclusions
In this study, self-reported LBP and NSP were already relatively common among adolescents. Girls have a higher risk for reporting LBP and NSP. Measures that are more effective in the prevention of LBP in male sports club members are needed. Excessive screen time is weakly associated with LBP and NSP, which should be taken into account in health promotion among adolescents.